'Nurse specialling': Direct nursing observation in the emergency department compared to other wards of an urban teaching hospital in Sydney. (June 2018) - Portelli, Maryssa; White, Bethany; Wand, Timothy; Haber, Paul S; Glozier, Nicholas
Objective: This study examined the patterns of direct observation of patients by nursing staff ('nurse specials') and compared those required for mental health/drug health (MH/DH)-related presentations to other patient groups in different care settings. Methods: A retrospective review of nurse special shifts requested during the 2014 calendar year at an urban teaching hospital. Results: Hospital-wide 14, 021 8-hour nursing shifts were ordered for special observation of patients, an average of 39 per day. Of these, 30% were requested for MH/DH-related presentations, with the majority (70%) required for medically unstable patients. However, of the 1917 shifts required in the emergency department, 1841 (96%) were for MH/DH presentations compared to 76 (4%) for patients with unrelated medical conditions (odds ratio 98.2; 95% confidence interval 77.71–124.06, P <0.0001). Conclusions: In contrast to the rest of the hospital, emergency department-based nurse special requests were significantly more likely to be for MH/DH presentations. This figure represents a considerable staff and financial burden and may be reduced by diversion or more rapid transfer of such presentations to an appropriate inpatient ward.